(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
During the Permian, climate experienced a change from icehouse to greenhouse conditions. Few multidisciplinary studies have investigated Kungurian (late Cisuralian) tropical terrestrial ecosystem and climate changes. Here, we apply an interdisciplinary approach to two alluvial-lacustrine successions of the Athesian Volcanic Group (Southern Alps, northern Italy) deposited in a Kungurian megacaldera during periods of volcanic quiescence. Sedimentological analysis combined with palynofacies studies allowed the reconstruction of the depositional environments. The study of sporomorph assemblages and stable organic carbon isotopes provided information on plant communities and the climate context. Two different depositional environments were present in the megacaldera: one proximal and one more distal with respect to the source, distinguished by a slightly different composition of the sediments, palynofacies and organic carbon isotopes. The plant community in the area was dominated by xeromorphic-hygromorphic taxa. The δ13Corgvalues are comparable to those of other Cisuralian continental organic matter and plants. The stable carbon isotope values show a small variability, which correlates weakly, but significantly, with the abundance of xeromorphic elements. All observations support deposition during semiarid to arid climate conditions, typical of the mid-late Cisuralian in the area.